2021
DOI: 10.1186/s12967-021-02891-6
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol has a unique effect on global brain activity: a pharmacological, functional MRI study in awake mice

Abstract: Background The phytocannabinoid cannabidiol (CBD) exhibits anxiolytic activity and has been promoted as a potential treatment for post-traumatic stress disorders. How does CBD interact with the brain to alter behavior? We hypothesized that CBD would produce a dose-dependent reduction in brain activity and functional coupling in neural circuitry associated with fear and defense. Methods During the scanning session awake mice were given vehicle or CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 118 publications
(129 reference statements)
0
15
0
Order By: Relevance
“…The unique patter of anisotropy between forebrain and hindbrain could reflect a reorganisation and resetting in the balance of the endocannabinoid signalling system 46,52 . In a recent study, we found a pattern of bipolar activation emphasising the hindbrain and forebrain in mice exposed to CDB 53 . The brain areas involved matched much of the distribution of NAPE‐PLD messenger RNA, an enzyme that increases anandamide levels when activated by CBD.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The unique patter of anisotropy between forebrain and hindbrain could reflect a reorganisation and resetting in the balance of the endocannabinoid signalling system 46,52 . In a recent study, we found a pattern of bipolar activation emphasising the hindbrain and forebrain in mice exposed to CDB 53 . The brain areas involved matched much of the distribution of NAPE‐PLD messenger RNA, an enzyme that increases anandamide levels when activated by CBD.…”
Section: Discussionmentioning
confidence: 66%
“…46,52 In a recent study, we found a pattern of bipolar activation emphasising the hindbrain and forebrain in mice exposed to CDB. 53 The brain areas involved matched much of the distribution of NAPE-PLD messenger RNA, an enzyme that increases anandamide levels when activated by CBD. Thus, THC in inhaled cannabis vapour and injection of CBD could both be impacting endocannabinoid signalling producing this unique brain pattern.…”
Section: Dwimentioning
confidence: 93%
“…An unexpected result was the hypometabolism in the region of the third ventricle and cerebellum in the group treated with the cannabidiol compared to baseline. This finding may be related to the migration of STZ injection and/or some action of CBD, for example, cerebellar deactivation [17].…”
Section: Discussionmentioning
confidence: 93%
“…In a just published study in mice treated with the phytocannabinoid cannabidiol (CBD) we reported a dose-dependent polarization of BOLD signal change along the rostral-caudal axis of the brain with the forebrain showing positive signal while the brainstem and cerebellum presented with negative signal ( Sadaka et al, 2021 ). The brainstem ascending reticular activating system (ARAS) was decoupled to much of the brain but was hyperconnected to the olfactory system and prefrontal cortex.…”
Section: Applicationsmentioning
confidence: 99%
“…Essentially baseline CBF is stable in awake rats regardless of stress, a critical point when measuring changes in functional signal dependent upon blood flow. In our more recent studies, we acclimate for five consecutive days, increasing the duration of acclimation with each subsequent day ( Sadaka et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%